2021
DOI: 10.32526/ennrj/19/2020225
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Polycyclic Aromatic Hydrocarbons and Bioaugmentation Potential of Locally Isolated Beneficial Microorganisms Consortium for Treatment of Tar-Balls

Abstract: Oil spills are one of the environmental pollutions that commonly occur along coastal areas. Tar-balls are one of the products that come from the oil spill pollution. In this study, tar-ball pollution was monitored at 10 points along the coastline of Marintaman Beach in Sipitang, Sabah, Malaysia. This research determined the physical characteristics, composition, and concentration of Polycyclic Aromatic Hydrocarbons (PAHs) in tar-balls. The total number of tar-balls collected was 227 (n=227). The tar-balls were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Comparative findings shown that present study is mostly exhibits lower degradation efficiency than the single strains in consortia. For instance, P. aeruginosa degraded 1 -21% more than in consortia due to supplement of biosurfactants and fertilizer, lower initial crude oil concentration or longer degradation period [9]. However, with 69.74% of crude oil removal or degradation efficiency, it can be concluded that current consortia culture is efficient.…”
Section: Biodegradation Efficiency Of Crude Oilmentioning
confidence: 98%
See 1 more Smart Citation
“…Comparative findings shown that present study is mostly exhibits lower degradation efficiency than the single strains in consortia. For instance, P. aeruginosa degraded 1 -21% more than in consortia due to supplement of biosurfactants and fertilizer, lower initial crude oil concentration or longer degradation period [9]. However, with 69.74% of crude oil removal or degradation efficiency, it can be concluded that current consortia culture is efficient.…”
Section: Biodegradation Efficiency Of Crude Oilmentioning
confidence: 98%
“…Biodegradation has emerged as one of the most promising technology in resolving the environmental problem due to increasingly research interests for biological degradation studies [8]. It can be defined as any degradation process that provoked by the action of microorganisms to return the contaminated environment to its original condition [9]. Compared with the conventional methods, biodegradation is a more sustainable option where it does not release toxic byproducts that can cause secondary pollution.…”
Section: Introductionmentioning
confidence: 99%
“…A spectrophotometer was used to record the data on optical density at 600nm. At their respective exponential phase, the dense cultures (1x10 7 ) were harvested for biodegradation studies [10].…”
Section: Determination Of Growth Curve Of Consortia Libemmentioning
confidence: 99%
“…Tourism activities are examples of recreation activities that helps a lot in increasing economic growth in Malaysia, especially in Sabah since here in Sabah we have a huge number of beautiful islands. Due to the improper handling of rubbish that may be derived from land and blown by winds, intentionally dumped from shore and ocean-based activities, the coastal and marine ecosystem especially in Sabah [1] is continuously threatened by this waste. Marine debris could be defined as any form of anthropogenic manufactured or processed materials discarded, disposed of or abandoned in the marine environment either deliberately or unintentionally, and may be transported to the ocean by river, drainage, sewage system or by wind [2].…”
Section: Introductionmentioning
confidence: 99%